A Supernumerary Nipple-Like Clinical Presentation of Lymphangioma Circumscriptum - Dustin Taylor; Natalie Kash; Sirunya Silapunt (Case Reports in Dermatological Medicine)
Lymphangioma circumscriptum is a superficially localized variant of lymphangioma. The characteristic clinical presentation is a “frogspawn” grouping of vesicles or papulovesicles on the proximal limb or limb girdle areas. Though most lymphangiomas develop congenitally, the lymphangioma circumscriptum subtype is known to present in adults. We report a case of lymphangioma circumscriptum on the left inframammary area of an African American female with an unusual supernumerary nipple-like clinical presentation. Our patient presented with a firm, smooth, hypopigmented papule, and the clinical diagnosis of keloid was made initially. However, she returned reporting growth of the lesion and was noted to have a firm, exophytic, lobulated, pink to skin-colored nodule. Histopathological examination demonstrated dilated lymphatic vessels, consistent with the diagnosis of lymphangioma. The presentation as a firm, hypopigmented papule and later exophytic, lobulated, skin-colored nodule in our case represents a clinical presentation of lymphangioma circumscriptum not previously described in the literature. Correct diagnosis in lymphangioma circumscriptum is vital, as recurrence following surgical resection and secondary development of lymphangiosarcoma and squamous cell carcinoma following treatment with radiation have been reported. Thus, it is important to consider lymphangioma circumscriptum in the differential of similar lesions in the future to allow appropriate diagnosis, treatment, and monitoring.